Champions in the age of COVID-19 - Wojtowicz, J.; Wolf-Root, A. (Sport, Ethics and Philosophy, 2021)
How should sport deal with prematurely ended seasons? This question is especially relevant to the current COVID-19 interruption that threatens to leave many leagues without champions. We argue that although there can be no winners, in certain situations there should be champions. Relevant to the current situation, we argue that Liverpool FC - currently with a 22+ point lead -should be crowned champions of the English Premier League. However, things are not as simple as simply handing the championship to whoever was in the lead when a season is prematurely ended. Through analogy with a fictional decathlon competition - and with the understanding that sporting seasons are themselves a type of game - we identify three reasons why leading at the moment of cessation is insufficient to be crowned a victor (of an individual event) or a champion (of a season-long competition): doing so fails to respect some valuable skills, fails to allow for luck to play out in an interesting way that affects competitions, and fails to respect competitive strategies. This discussion can then inform determining what, if any, end-of-season accolades are relevant, such as championships, relegation, or promotion. No team can win in a league that has failed to be completed, but there can still be a champion.